Manfaat Air Rebusan Cengkeh Untuk Mengurangi Mual Muntah Pada Ibu Hamil - Pohan, Atika; Hasibuan, Usti Fina Hasanah (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
Pregnancy is a physiological part of a woman's life. Pregnancy is usually accompanied by discomfort, where the discomfort that pregnant women often experience, especially in the first trimester, is nausea and vomiting (emesis gravidarum). Research objective To determine the benefits of giving boiled clove water (Syzygium aromaticum) to reduce the frequency of nausea and vomiting in early trimester pregnant women at the Murniati Clinic in 2023. Method in this activity is counseling for pregnant women in the first trimester. Result Giving boiled clove water has been proven to be effective in reducing the intensity of nausea and vomiting in pregnant women in the first trimester at the Murniati Clinic in 2023. Conclusio There are benefits of giving boiled clove water in reducing the frequency of nausea and vomiting. vomiting in early trimester pregnant women.